Practical Work on The Transition of The Educational Process in Higher Educational Institutions to The Stage-Stage Credit-Module System and Their Results - Khamitovna, Khakimova Khulkar (Bumi Publikasi Nusantara, 2022)
The purpose of this research was to examine the importance and role of thinking design in accelerating creative activity in a variety of industries from the education point of view, starting with scientific and more popular sources. This article discussed methods for investigating the factors and origins of innovative growth. Its goal is to ensure that proper methods are used to manage competitiveness and innovative sustainable development at the same time while taking into account the degree of entrepreneurial structure. Innovation development takes precedence over the best condition of management, which is followed by labor productivity.